When Citizen Mobilisations Transform the Andean Foothills: the Case of the Group for the Defence of the Precordillera - Consuelo Biskupovic; Caroline Stamm (Revue de Géographie Alpine)
The Andean foothills found on the outskirts of Santiago are mainly private property. The management of this area has been an issue of conflict between residents and developers. Using the example of the municipality of La Florida, this article focuses on how conflict over the Andean foothills goes beyond simple land-use issues to create a new relationship with the “mountain” and new forms of land management. Combining ethnography and geography, this text highlights the role of the Andean foothills’ peculiar characteristics in the collective demands of citizens committed to their protection and conservation. It also discusses the role of conflict in creating and amplifying territoriality and as a process of (concrete as well as abstract) territorialisation and innovation in itself. The development of a community park that is neither private nor public highlights how innovative solutions can emerge from these citizen mobilisations.